2017
DOI: 10.1519/jsc.0000000000001672
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of Exercise Training Following the Use of a Birthing Ball During Pregnancy and Delivery

Abstract: Fournier, D, Feeney, G, and Mathieu, M-E. Outcomes of exercise training following the use of a birthing ball during pregnancy and delivery. J Strength Cond Res 31(7): 1941-1947, 2017- Using a birthing ball (BB) is an exercise form that is growing in popularity. Improved delivery outcomes have been recently reported with as little a 6-8 hours of training per week; however, little is known regarding lower and higher training levels. The aim of this study was to document whether more time spent training with a BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
1
8
1
2
Order By: Relevance
“…It was also statistically significant that the experimental group was more effective in reducing pain childbirth than the control group [32]. In another research, Birth ball exercise were also done for 30 minutes in the childbirth group [33]. The subject of the research is divided into two group, they were experimental group which experienced pain during childbirth latent phase at the interval of 15-20 minutes and dilatation of the cervical 0-4 of cm and the control group with no pain delivery by the score of VASs (Visual Analogue Scales) 0 but secreted mucous blood.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…It was also statistically significant that the experimental group was more effective in reducing pain childbirth than the control group [32]. In another research, Birth ball exercise were also done for 30 minutes in the childbirth group [33]. The subject of the research is divided into two group, they were experimental group which experienced pain during childbirth latent phase at the interval of 15-20 minutes and dilatation of the cervical 0-4 of cm and the control group with no pain delivery by the score of VASs (Visual Analogue Scales) 0 but secreted mucous blood.…”
Section: Resultsmentioning
confidence: 88%
“…Each exercise session takes 20 minutes and is carried out up to three times over six weeks, equipped with media containing a video duration of 19 minutes and a booklet of 26 pages (based on the results of the review and recommendations by two prenatal educators and certified deliveries, two body specialist and one physical therapist) and birth ball exercise during labor (Exercise, comfortable positions and movements must be supported every hour) and follow-up provided a statistically proven improvement with a significant result in pain during labor [31]. From the results of studies in the experimental group as evidenced by statistically significant tests about 30 minutes of ball exercise in the latent phase can reduce back pain and lower abdomen, reduce labor pain in the latent phase and hypertension [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,48,49 Furthermore, recent quasi-experimental study was conducted by Fournier et al in 2016 have found negative correlation between total training time on the birth ball exercise and total labor time (r= -0.408; p= 0.031), in other word, an increased training times with a birth ball during pregnancy was associated with shorter labor duration for both stage 1(r= -0.372; p= 0.043) and stage 2 (r= -0.415; p= 0.028). [50][51][52] The most of studies have their limitation in terms of including the concomitant use of other non-pharmacological pain relief during labor, but not specifically investigating the combination between clinical hypnoanalgesia and birth ball exercise itself. One of RCT has been conducted by Henrique et al in 2016 assessed the influence of perineal exercise using birth ball in combination with warm bath or hypnotherapy.…”
Section: Birth Ball Exercises and Posturementioning
confidence: 99%
“…[6,8] One of the relaxation techniques and other non-pharmacological actions in handling pain during childbirth is by using birth ball exercises which are also commonly known in Pilates exercises as fitball, Swiss ball and petzi ball. [5,9,11] To prove the influence of both technique of counter pressure massage and birth ball exercise methods on labor pain, it is necessary to combine the two methods in order to obtain a stronger effect in stimulating the β-endorphin hormone and the relaxation effect will be more maximal so that the increase in intensity decreases labor pain will be optimal. [8,10,14] Counter pressure can be applied in lying down position or half-sitting position, depends on the comfort of the mother position.…”
Section: Introductionmentioning
confidence: 99%